High-rate in-vessel continuous composting of olive mill byproducts. (September 2022) - Manthos, Georgios; Zagklis, Dimitris; Papapanou, Melina; Zafiri, Constantina; Kornaros, Michael
Graphical abstract: Highlights: Two-phase olive pomace is a waste stream that needs alternative treatment methods. High-rate continuous composting alongside other olive byproducts was tested. The material was stable after a retention time of 14 d inside the composter. After six weeks of maturation the compost product had the desired characteristics. Elimination of residual pathogens in the product should be further investigated. Abstract: The increasing production of agro-industrial organic residues in modern society is extremely concerning. One of the most polluting procedures in the agricultural industry is the production of olive oil. This process creates a large amount of waste with high organic load and phytotoxic components. In this study, composting of two-phase olive pomace (OP), olive leaves (OL) and dewatered anaerobic sludge (DAS) from an olive mill wastewater anaerobic digestion process was conducted in a pilot-scale in-vessel high-rate continuous composter. Five different feed scenarios were studied with different OP/OL ratio in the feed material, while the effect of the addition of pine tree bark pieces (PB) and DAS was examined. The OP:OL 95:5 % w/w ratio exhibited the best results in terms of product quality, while OL proved capable of acting as a bulking agent for the better aeration of the material. The final product in the optimum feed ratio was free of Salmonella spp., was stable in terms of static respiratory index (lower than 0.5 g O2 kg −1 VS h −1 ) but contained elevated E. coli levels (3.5 × 10 4 CFU g -1 with a limit of 1 × 10 3 CFU g -1 ), which was the only EU proposed compost quality criteria not met. The addition of a more easily degradable material in the feed mixture is expected to lead to elevated composting temperature and amend the presence of pathogens.